2023
DOI: 10.1021/acsomega.2c06489
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of High-Strength and Excellent Compatibility Fluorine/Silicone Rubber Composites under the Synergistic Effect of Fillers

Abstract: Fluorine/silicone composite rubber is widely used as a sealing material in aerospace, missile, automotive, petroleum, and other industries, but the traditional process does not use synergistic fillers to strengthen the composite system. In this research, fumed SiO2 and black caron (N990) were used as synergistic fillers, fluorine/silicone composite rubber was prepared by mechanical mixing process, and three different fluorine rubber systems were used to find the best composite material. The mechanical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In the case of FSE compounds containing graphenic materials, the enhanced properties are likely attributed to the interfacial compatibility between graphene and the fluorinated groups of FSE. Comparable results have been reported for fluoroelastomers, such as FKM …”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…In the case of FSE compounds containing graphenic materials, the enhanced properties are likely attributed to the interfacial compatibility between graphene and the fluorinated groups of FSE. Comparable results have been reported for fluoroelastomers, such as FKM …”
Section: Resultsmentioning
confidence: 55%
“…Comparable results have been reported for fluoroelastomers, such as FKM. 41 Figure 3e presents the results of the hardness and abrasion resistance of FSE compounds. The hardness of FSE is approximately 45 Shore A, being this value slightly lower than that reported in the literature, probably due to the type of crosslinking agent used.…”
Section: Mechanical Properties Hardness and Abrasionmentioning
confidence: 99%
“…5 In addition, a small amount of rGO (0.5 wt%) hinders the thermal oxidative degradation of the fluoro silicone rubber that is commonly used in aerospace, military, and automotive industry which commonly operate at elevated temperature. 179,180 The tensile strength of the rGO/fluoro silicone rubber after aging at 230 °C for 3 days is maintained at 87.5% while the initial weight after aging at 350 °C for 12 hours is successfully maintained at 90%. The proposed mechanism suggested that the route of auto-oxidative degradation is blocked by the rGO which scavenges the primary free radical generated by cleavage of the fluoro silicone rubber side group.…”
Section: Graphene Materials and Their Hybrids' Application In Various...mentioning
confidence: 99%
“…FSIR has methyl, vinyl and trifluoropropyl side chains, which improve the oil and solvent resistance of the rubber due to the electronic effect and the good shielding effect of the C-F bond on the C=C bond [ 25 , 26 ]. It also has a wide operating temperature range of −60–200 °C and can be operated in cold environments [ 27 ].…”
Section: Introductionmentioning
confidence: 99%